PEMBELAJARAN BERNYANYI DI SMP NEGERI 1 BAYANG KABUPATEN PESISIR SELATAN - Noni Veronika; j Lumbantoruan; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to describe the learning process of singing in the subjects of art and culture, especially in the teaching material of national anthem in Junior High School No 1 Bayang. This research was qualitative research through a descriptive approach. The implementation of learning singing in that school can be described as follows: in the first meeting, the teacher explained the material about singing. In the second meeting, the teacher explained how to sing with the correct vocal techniques, and explained how to use the techniques of breathing in singing. In the third meeting, the students sang the song my Tanah Airku. The result of research in learning singing at junior high school no 1 Bayang, South Pesisir Regency was : (1) In implementing of learning singing, the teacher used lecturing method. This was irrelevant to the learning topic, (2) Teachers have not had the planning which is standardized, (3) the implementation of strategies has not optimal yet, (4) The approach of learning that teachers done was less relevant, (5) Learning methods have not been effective. The impact of the above five indicators of students ' ability in singing has not been adequate. Keywords: Learning, Singing